Transcriptomic and Biochemical Analysis Reveal Integrative Pathways Between Carbon and Nitrogen Metabolism in Guzmania monostachia (Bromeliaceae) Under Drought - Gonçalves, Ana Zangirolame; Mercier, Helenice (Frontiers in Plant Science, 2021)
Most epiphytes are found in low-nutrient environments with an intermittent water supply. To deal with water limitation, many bromeliads perform crassulacean acid metabolism (CAM), such as Guzmania monostachia, which shifts from C3 to CAM and can recycle CO2 from the respiration if stomata remain closed during daytime and nighttime (CAM-idling mode). Since the absorbing leaf trichomes can be in contact with organic (urea) and inorganic nutrients (NO3-, NH4+) and the urea hydrolysis releases NH4+ and CO2, we hypothesized that urea can integrate the N and C metabolism during periods of severe drought. Under this condition, NH4+ can be assimilated into amino acids through GS, while the CO2 can be pre-fixated by PEPC. In this context, we evaluated the foliar transcriptome of G. monostachia to compare the relative gene expression of some genes involved with CAM and the N metabolism when bromeliads were submitted to 7d of drought. We also conducted a controlled experiment with an extended water deficit period (21d) in which bromeliads were cultivated in different N sources (urea, NH4+, NO3-). Our transcriptome results demonstrated an increment in the expression of genes related to CAM, particularly those involved in the carboxylation metabolism (PEPC1, PPCK, NAD-MDH), the movement of malate through vacuolar membrane (ALMT9), and the decarboxylation process (PEPCK). Urea stimulated the expression of PEPC1 and ALMT9, while Urease transcripts increased under water deficit. Under this same condition, GS1 gene expression increased, indicating that the NH4+ from urea hydrolysis can be assimilated in the cytosol. We suggest that the link between C and N metabolism occurred through the supply of carbon skeleton (2-OG) by the cytosolic isocitrate dehydrogenase since the number of NADP-ICDH transcripts was also higher under drought conditions. These findings indicate that while urea hydrolysis provides NH4+ that can be consumed by GS1/GOGAT cycle, the CO2 can be used by CAM, maintaining photosynthetic efficiency even when most stomata remain closed 24h (CAM-idling) as in the case of a severe water deficit condition. Thus, we suggest that urea could be used by Guzmania monostachia as a strategy to increase its survival under drought, integrating N and C metabolism.